An energy screening and morphology characterization-based hybrid expert scheme for automatic identification of micro-sleep event K-complex. (April 2021) - Zhao, Xian; Chen, Chen; Zhou, Wei; Wang, Yalin; Fan, Jiahao; Wang, Zeyu; Akbarzadeh, Saeed; Chen, Wei
Highlights: A novel hybrid expert scheme to identify sleep micro-event K-complex is proposed by integrating signal morphology with expert knowledge into the decision-making process. A rapid screening process of potential event candidates is devised by combining TEO-based energy and personalized thresholds, which can eliminate artifacts or other sharply contoured waveforms and minimize the individual variability in raw EEG signals. Characteristic components of events are separated from EEG signals using new filtering frames of morphological filters. The judgment rules driven by expert knowledge are employed for finding events from morphological features and location information. Besides the occurrence of K-complexes, their location and duration can also be predicted by the proposed scheme. Abstract: Background and Objective: : K-complexes, as a significant indicator in sleep staging and sleep protection, are an important micro-event in sleep analysis. Clinically, K-complexes are recognized through the expert visual inspection of electroencephalogram (EEG) during sleep. Since this process is laborious and has high inter-observer variability, developing automated K-complex detection methods can alleviate the burden on clinicians while providing reliable recognition results. However, existing methods face the following issues. First, most work only identifies the K-complexes in stage 2, which requires distinguishing the sleep stages as the prerequisite for further events' identification. Second, most approaches can only detect the occurrence of events without the ability to predict their location and duration, which are also essential to sleep analysis. Methods: : In this work, a novel hybrid expert scheme for K-complex detection is proposed by integrating signal morphology with expert knowledge into the decision-making process. To eliminate artifacts, and to minimize the individual variability in raw sleep EEG signals, the potential K-complex candidates are first screened by combining Teager energy operator (TEO) and personalized thresholds. Then, to distinguish signal shapes from background activity, a novel frame of filtering based on morphological filtering (MF) is devised to differentiate morphological components of K-complex waveforms from EEG series. Finally, K-complex waveforms are identified from the extracted morphological information by judgment rules, which are inspired by expert knowledge of micro-sleep events. Results: : Detection performance is evaluated by its application on the public database MASS-C1 (Montreal archives of sleep studies cohort one) which includes the recordings of 19 healthy adults. The detection performance demonstrates an F-measure of 0.63 with a recall of 0.81 and a precision of 0.53 on average. The duration error between events and detections is 0.10 s. Conclusions: : The presented scheme has detected the occurrence of events. Meanwhile, it has recognized their locations and durations. The favorable results exhibit that the proposed scheme outperforms the state-of-the-art studies and has great potential to help release the burden of experts in sleep EEG analysis.